THE INFLUENCE OF OCCUPATIONAL HEALTH AND SAFETY (OHS), WORK ENVIRONMENT, AND WORKLOAD ON EMPLOYEE PERFORMANCE AT PT. ASURANSI BHAKTI BHAYANGKARA - Nur Endah Sabarini; Dewi Puspaningtyas Faeni (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2024)
The aim of this research is to analyze the influence of Occupational Safety and Health (OSH), work environment, and workload on employee performance at PT. Asuransi Bhakti Bhayangkara. Occupational Safety and Health (OSH) is a crucial factor that can affect employee performance, as a safe and healthy work environment can enhance productivity and work efficiency. Moreover, a conducive work environment plays a significant role in boosting employee morale and motivation. A balanced workload will have a positive effect on performance, whereas excessive workload can cause stress and reduce productivity. This research uses a quantitative method with a survey approach. Data were collected through questionnaires distributed to employees of PT. Asuransi Bhakti Bhayangkara. Data analysis was conducted using multiple linear regression to determine the influence of each independent variable on employee performance. The results of the study indicate that Occupational Safety and Health (OSH) has a significant impact on employee performance. The work environment also proves to have a significant impact on performance. Meanwhile, workload shows a negative and significant influence on employee performance. The conclusion of this study is that to improve employee performance, the company needs to pay attention to and enhance factors such as Occupational Safety and Health (OSH), create a comfortable and conducive work environment, and manage employee workload to avoid overburden.